The Effect of Participative Leadership on Organizational Commitment with Impact on Work Productivity Vocational School Teachers in Mataram City - Jaelani, Abdul Kadir; Agung, Anak Agung Gede; Yudana, I Made; Dantes, Kadek Rihendra (International Journal of Membrane Science and Technology, 2023)
The productivity of vocational school teachers in Mataram City is low, teacher performance is influenced by head leadership and work motivation. The purpose of this study was to determine the effect of participatory leadership on organizational commitment and its impact on the work productivity of vocational schoolteachers in Mataram City. This research method is quantitative. The technique of determining the sample was 721 people randomly based on Morgan's theory confirmed by the Warwick and Lininger formula to obtain data for 259 teachers. Hypothesis analysis using Structural Equation Modeling - Partial Least Squares technique. The results of the study are; (1) participative leadership has a direct positive and significant effect on organizational commitment as evidenced by the T-Statistic 7.835 and P-Values 0.000; (2) participative leadership has a direct positive and significant effect on teacher performance as shown by the T-Statistic 7.007 and P-Values 0.000; (3) organizational commitment has a direct positive and significant effect on teacher performance shown T-Statistic 2.226 and P-Values 0.012 (4) participative leadership has an indirect effect on work productivity through organizational commitment with T-Statistic 2.606 and P-Values 0.009. The finding of this study is that organizational commitment mediates the effect of participatory leadership on the work productivity of vocational school teachers in Mataram City. It is concluded that participative leadership affects organizational commitment and organizational commitment.